2021
DOI: 10.3390/ma15010269
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Cause of Toxicity of Silicone Oil?

Abstract: Purpose: To investigate the toxicity of the low-molecular-weight components (LMWCs) in ophthalmic silicone oils (SilOils) on retinal cell lines. Methods: The toxicity of six types of LMWCs were studied and compared with conventional SilOil 1000 cSt. In vitro cytotoxic tests of LMWCs, in both liquid and emulsified forms, on three retinal cell lines (Müller cells (rMC-1), photoreceptor cells (661W) and retinal pigment epithelial cells (ARPE-19)) were conducted using a transwell cell culturing system. The morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
2
9
0
1
Order By: Relevance
“…As shown in Figure , the SiR catheters after silicone oil infusion showed a decrease in viable cells ( p < 0.05). A similar finding has also been reported by Handa et al A recent study revealed that most silicone oil contains chemical impurities (e.g., low-molecular-weight components) that may diffuse into cells and cause cytotoxicity, but definitive clinical evidence of silicone oil toxicity is still lacking. The silver deposition on either SiR or SiO catheters induced no significant decrease in viable cells ( p > 0.05) despite the fact that the AgO catheters released a relatively higher level of Ag + within 24 h (Figure h).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure , the SiR catheters after silicone oil infusion showed a decrease in viable cells ( p < 0.05). A similar finding has also been reported by Handa et al A recent study revealed that most silicone oil contains chemical impurities (e.g., low-molecular-weight components) that may diffuse into cells and cause cytotoxicity, but definitive clinical evidence of silicone oil toxicity is still lacking. The silver deposition on either SiR or SiO catheters induced no significant decrease in viable cells ( p > 0.05) despite the fact that the AgO catheters released a relatively higher level of Ag + within 24 h (Figure h).…”
Section: Resultsmentioning
confidence: 99%
“…However, once coated by surfactants, the small droplets may remain dispersed and sneak through retinal tears into the subretinal space or the zonules in the anterior segment [ 9 , 19 , 59 , 60 ]. This phenomenon can lead to other complications such as inflammation, corneal endothelial damage, high IOP, glaucoma, optic neuropathy and even retinal toxicity [ 61 , 62 ].…”
Section: Physical Properties Of the Currently Available Vitreous Subs...mentioning
confidence: 99%
“…PDMS’s quality and purification is crucial for obtaining a stable and non-toxic SiO for use in vitreoretinal surgery, and it is today known that SiOs can have a low long-term toxic effect on the eye tissues, and even to the tissues surrounding the eye globe. Finding a solution to that is still an ongoing topic of research [ 62 , 91 , 92 , 93 ].…”
Section: Chemical Properties Of the Currently Available Tamponades An...mentioning
confidence: 99%
“…In particular, LMWC, short-chain siloxane oligomers or polymers, have long been investigated due to their potentially harmful properties, being able to act as emulsifiers of SO and to diffuse from the vitreous cavity into ocular tissues [ 44 ]. Moreover, three of them, namely the cyclic LMWCs, octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5) and dodecamethylcyclohexasiloxane (D6), have been recognized as toxic by the European Chemicals Agency ( , accessed on 30 May 2022) and show acute cytotoxicity in vitro at high concentration [ 45 ]. Despite the fact that, when testing a concentrate of LMWC with MW up to 1557 g/mol, no acute cytotoxic effect was detected, the long-term effects of these compounds are still unknown [ 46 ].…”
Section: Structural and Physico-chemical Findingsmentioning
confidence: 99%